THE POTENTIAL OF TURMERIC RHIZOME EXTRACT AS ANTIBIOFILM AGAINST Staphylococcus aureus THROUGH IN SILICO AND IN VITRO APPROACHES - Aji Nur; Risnawati Risnawati; Rahmaan Naufal Maulana; Tabina Nadine Elysia (Pharmacoscript, 2026)
Escalating antibiotic resistance in Staphylococcus aureus is driven by biofilm formation, which undermines the efficacy of antibiotics. This study evaluated curcumin from turmeric (Curcuma longa L.) as a natural antibiofilm agent using in silico and in vitro methods. Molecular docking and toxicity predictions were used to test curcumin's interaction with S. aureus biofilm proteins. In vitro efficacy was measured by disc diffusion and crystal violet staining assays. In silico analysis identified LuxS (PDB ID: 5V2W) as a viable target. Docking validation yielded an RMSD of 3.00 Å and identified 10 potential ligands, including curcumin, auratiamide, and chlorogenic acid. Phytochemical profiling showed that the ethyl acetate fraction had the highest curcuminoid content (24.88% w/w), higher than the 70% ethanol extract (21.69% w/w) and the methanol fraction (0.83% w/w). The ethyl acetate fraction showed moderate antibacterial activity but the strongest antibiofilm effects, with a minimum biofilm inhibitory concentration (MBIC) of 0.05% and an IC50 of 0.01%. In conclusion, the ethyl acetate fraction of turmeric enriched with curcuminoids shows strong potential as a natural antibiofilm agent. Computational and experimental evidence support this. These findings suggest the fraction is a promising candidate for topical antibiofilm development. Future research should focus on formulating this fraction in topical delivery systems and testing its efficacy in ex vivo skin or dermal infection models to assess clinical potential.